The transition to a circular economy as a competitive advantage in the textile manufacturing SME in Tlaxcala, Mexico - Sarmiento Paredes, Susana; Carro Suárez, Jorge; Nava, Doroteo (Acta Universitaria, 2022)
Faced with the environmental crisis, companies require production models that mitigate climate change and represent a competitive advantage, with the circular economy being an alternative. The objective of this study was to determine if the principles of circular economy: to preserve and improve natural capital, to optimize the performance of resources, and to promote the effectiveness of the system represent a competitive advantage, taking as object of study the textile small and medium-sized enterprises (SME) of Tlaxcala, Mexico. The methodology consisted of making a diagnosis on the perception of the variables. Subsequently, a descriptive and variance analysis, a Tukey test, a correlation analysis, and a regression analysis were performed to determine their significance and relationship. The results revealed that the circular economy principles will allow the SME to perform better than the competition, making it different and lowering its costs. It is concluded that the circular economy can impact environmental care and competitiveness.